The whole land belongs to men: Galician Teachers, Political Exile and Teaching Action - Ferreiro Fente, Xosé Gregorio (Historia y Memoria de la Educación, 2019)
Although it is legitimate to state that the existing literature regarding the Galician republican exile provides us with a satisfactory account, due to its abundance and quality, we also believe that the subject remains unfinished in many of its chapters. One aspect that unquestionably demands more study has to do with the situation in Galicia of the exile of its teachers. Starting from this premise, we also believe that the issue of Galician exile has frequently been addressed from perspectives that were not entirely appropriate. In this article we would like to offer a rough sketch, a sort of “bird’s eye view” of the phenomenon of teachers’ exile, highlighting the elements that make it unique in relation to other Spanish exiles ― especially those originating in territories that were under the government’s legal authority after the coup d’état in July 1936―. As a narrative resource, we will sometimes resort to the biographical accounts of teaching figures whose journeys and ordeals ultimately serve as paradigmatic and educational examples of the specific fact which is the object of our attention. Furthermore, the fact of mentioning some of their names implies, indirectly, the first step in a more complete onomastic catalogue than we currently have of the many teachers from Galicia that were sent into exile.